Pengaruh Hutang Jangka Pendek Dan Hutang Jangka Panjang Dalam Menilai Kinerja Perusahaan Dari Aspek Profitabilitas - Supriadi, Yoyon; ALFIANA, M. NUR (LPPM Institut Bisnis dan Informatika Kesatuan, 2014)
Firms are facing dificulties in running business if only using internal source of funds. The growth or development of a company results in the need for greater funding. Hartono (2000, 254), mentions that the debt contains risk. The higher the risk of a company, the higher the level ofprofitability expected in retumfor the high risk and conversely the lower the risk of the company, the lower the level of profitability expected in return for lower risk. This study tries to investigate the effect of short and long term debts on company's performance when viewed from its profitability aspect. The results showed that simultaneous independent variables Y1(Return on Assets) and the independent variable Y2 (Return On Equity) there is no significant effect on the independent variable. The coeficients determinations show that there are other variables that determine the returns or profitability. Based on the establishment of the regression equation suggests that if there is an addition of one - unit on the coefficients Change of Debt Short - Range and the Longterm Debt Equity Retum on Assets will decrease, as well as in the event ofone - unit increments of the coefficients Change of Debt Short - Range Longterm Debt Equity and the Retum On Equity will decline . Keywords: long-term debt, profitability